Higher education and the efficiency analysis of Canadian public policies - Costa, Danilo de Melo (Contextus - Revista Contemporânea de Economia e Gestão, 2018)
This research analyzes the effectiveness of public policy funding mechanisms for higher education in Canada in the period from 2003 to 2012, assuming a gap to be explored concerning the proposition of new public policies that contribute to financing higher education worldwide. When it comes to the methodological procedures, this study was designed as exploratory and quantitative. A group of public policies were statistically analyzed, using as a reference the compound annual growth rate (CAGR), which was in turn based on the investments made and the number of students attended in the period. The results showed that Canada has proven to be a country of solid and well-defined public policies, which had an impact on its good performance, with an emphasis on: the CESG policy, which presents the proactive way to ensure access to, and presence of, young people in higher education; CSGP/CSLP, which was statistically significant in relation to the percentage of students attended; and OSAP / Reaching Higher policy, which was more sensitive to the needs of the context in which it is inserted (Ontario province).